Robotic-assisted complete mesocolic excision, central vascular ligation and para-aortic lymph node dissection in multifocal carcinoid: A case report and technical description. (2020) - Young, R.; Rajkomar, A.; Smart, P.; Warrier, S.
Highlights: Neuroendocrine tumours are the most common type of small bowel neoplasm. Robotic technique may be superior to open technique for lymph node dissection. Robotic-assisted complete mesocolic excision is a safe and effective technique. Abstract: Introduction: Neuroendocrine tumours are the most common type of primary small bowel neoplasm. Consensus guidelines recommend a multimodal approach to treatment of such tumours, with aggressive surgical resection remaining the mainstay of management. There is evidence that complete mesocolic excision (CME) of lymph nodes is associated with superior oncological outcomes including longer disease-free survival in patients with colorectal cancer than standard lymph node dissection and there is increasing evidence to suggest that the robotic approach may be superior to laparoscopic or open CME. This report discusses a robotic-assisted approach to CME with central vessel ligation (CVL) and para-aortic lymph node dissection in a case of multifocal neuroendocrine tumour of the small bowel. Presentation of case and technical approach: This report details the case of a 73-year-old male with multifocal small bowel neuroendocrine tumour. He underwent a robotic-assisted right hemicolectomy, small bowel resection, CME, CVL and para-aortic lymph node dissection. The approach described involved undertaking CME, CVL and bowel resection with a standard right hemicolectomy robotic set-up before re-docking the robot to perform the retroperitoneal para-aortic lymph node dissection. Discussion: This case highlights the management of multifocal small bowel neuroendocrine tumour using a robotic approach for surgical resection and lymph node clearance. Conclusion: The robotic approach provides a safe and effective technique for undertaking surgical resection of small bowel neuroendocrine tumour as well as complete mesocolic excision of lymph nodes. With a change in port positions, a robotic approach can be utilised for CME/CVL as well as retroperitoneal node dissection.